Recent diagnostic developments at the 100 kJ-level laser facility in China - Feng Wang (Matter and Radiation at Extremes, 2020)
A 100 kJ-level laser facility has been designed to study inertial confinement fusion physics in China. This facility incorporates various diagnostic techniques, including optical, x-ray imaging, x-ray spectrum, and fusion product diagnostics, as well as general diagnostics assistance systems and central control and data acquisition systems. This paper describes recent developments in diagnostics at the facility.